INSTITUTIONAL EVALUATION: ANALYSIS OF SYSTEM EVALUATION AND THE NEED FOR POLITICAL LEGITIMACY - Padua Sabia, Claudia Pereira de [UNESP] (Univ Estadual Sudoeste Bahia, 2019)
Large-scale evaluation has come a long way since the 1990s and despite the criticisms and contradictions that the issue involves, the debate about its results, formats and consequences of its implementation in the classroom has been broadened. The system evaluations have been informing from their first editions that the learning is not happening in the basic education of our schools of the country. The study aims to reflect on the results of the external evaluation by the school actors in the institutional evaluation aiming its use for pedagogical planning. It is the institutional evaluation that allows the political legitimacy of the data available in the external evaluation through negotiation between those who do the school. Although the emphasis in this work on institutional evaluation has been to reflect the results of the system evaluation, we emphasize the need for other qualitative indicators listed by the collective that contribute to the recovery of the purpose of the school. The methodology used is bibliographical and documentary research. As a result, we present the growth of evaluation surveys for pedagogical support, the improvement of the Pedagogical Bulletins prepared by the State Secretariats of Education, as well as some initiatives such as the PIP - Pedagogical Intervention Plan and the Monitoring of Learning.
Keywords: Large scale evaluation; Institutional Evaluation; National Evaluation System